An Action Research Project on The Use of Facebook in an Undergraduate Visual Communication Study Unit - Souleles, Nicos (My University, 2012)
This article describes a technical action research project on how Facebook can be embedded in the structure of an undergraduate visual communication study unit. It identifies educational benefits as well as pitfalls, and how students perceive this Social Networking Site (SNS) as part of their teaching and learning process. Data was collected through an online questionnaire, content analysis of Facebook posts and a focus group. The limitations of this investigation relate to the generalizability of findings that are the result of action research. Students identified a range of educational benefits relating to peer-to-peer but also teacher-student support. Among the challenges were student attitudes and perceptions of what should or should not occur with the Facebook group when used for teaching and learning. This article provides a blueprint for the next cycle of the action research process, which can include specific refinements, but also needs to consider a number of challenges.
Keywords: Content analysis; Facebook; Higher education; Social networking sites; Technical action research; Visual communication